Influence of oscillating fiber laser welding process parameters on the fatigue response and mechanical performance of butt-jointed TWIP980 steels - Cavusoglu, Oktay; Aydin, Hakan; Eroglu, Mehmet; Davut, Kemal (Walter de Gruyter Gmbh, 2025)
In this study, the effect of laser power, welding speed, linear heat inputs on the mechanical performance of TWIP980 steels joined by oscillating fiber laser welding in butt welding configuration was investigated. Oscillating fiber laser welding were changed: laser power from 1.2 to 1.6 kW, welding speed from 20 to 30 mm s-1, linear heat input from 40 to 80 J mm-1. The tensile, hardness and fatigue tests were carried out to determine mechanical performance. A significant improvement in weld penetration, fatigue performance and mechanical properties was detected at linear heat inputs above 53.33 J mm-1. The best mechanical properties were obtained at 1.6 kW laser power and 25 mm s-1 welding speed. The study reveals that linear heat inputs, laser power, and welding speed have significant effects on mechanical performance and weld geometry. Furthermore, the results demonstrate that oscillating fiber laser welding enables good weldability even at low laser power.
Keywords: oscillating laser welding; fiber laser welding; high manganese steel; TWIP steel; mechanical properties